"Let Your Voice Lead You": Critical Community-Building to Support the Writing of Recently Resettled Youth. (2nd October 2021) - Zoch, Melody; Marhatta, Pratigya; Vetter, Amy; Faircloth, Bev; McDaniel, Dominique
Abstract : This study examines the use of critical community-building—using dialogue as a collective to support, listen to, ask questions, and assist each other in thinking in critical ways—to support resettled youths' writing during a summer writing camp. Through encouraging the youth to use their home languages, by celebrating their cultures, honoring their experiences, and fostering peer relationships, we established a sense of community and a supportive writing space. The authors offer insights into their work and implications for educators in more traditional classroom spaces as well.